Electrical Impedances Variations Values in Patients with Cochlear Implant - Oana Manolache; Raluca Olariu; Luminita Radulescu; Sebastian Cozma (Romanian Society of Oral Rehabilitation, 2012)
Introduction Identifying the impedance values in the post-surgery care of cochlear implanted patient, provide useful information to adjust the settings of the sound processor for the best possible auditory perception. Material and methods We investigated changes in impedance values of the intracochlear electrodes implanted in 72 patients over a period of 3 months. The measurement was carried out using computer hardware and software interfaces from cochlear implant producers. Results In absence of electrical stimulation, there is an increase of impedance on all electrodes of all cochlear implant models. After activation, the impedances values variations are depending on the type of the device. Conclusions The intraoperatory impedance values and their fluctuations are part of the postoperative common trends for each specific brand. Besides the parameters related to the device, the individual organic features of the inner ear may play an important role in the distribution of electrical impedance profile.